Accelerating the Increase of Functional Positions of Lecturer at Pekalongan University - Luthfia Qothrun Nada; Sutarto, Joko; Pramono, Suwito Eko (Educational Management, 2024)
This research aims to: 1) describe lecturers' understanding of career development through functional positions; 2) identify the obstacles they face in the promotion process; and 3) analyze strategies to accelerate these promotions. Lecturers are key human resources in universities, involved in education, research, and community service as part of the Tri Dharma of Higher Education, which supports their career development. However, at Pekalongan University, many lecturers face delays in being promoted to functional positions. The method used in this research is qualitative research. Data collection methods include observation, interviews and document study. The data validity technique used is triangulation. Meanwhile, the data analysis technique uses data reduction, data display, drawing conclusions and verification. The results of this research are: 1) Lecturers' understanding of career development through functional positions is not yet fully understood. . Lecturers have been given direction and guidance regarding the implementation of the Tri Dharma of Tinngi College to support lecturer careers, especially for promotion to functional positions. However, in practice, lecturers still have difficulty meeting the credit threshold, especially in the field of conducting research. Apart from that, administrative obstacles are also the reason why lecturers are reluctant to prepare documents for promotion to functional positions; 2) There are 3 (three) obstacles for lecturers in applying for promotion to functional positions, namely individual lecturer obstacles, agency support and LLDIKTI and DIKTI policies in the Credit Score Assessment system; 3) Acceleration of promotions to functional positions carried out by Pekalongan University by implementing strategic management which includes the strategy formulation stage, strategy implementation stage and strategy evaluation stage.